Preparing students for an evidence-based health service: A collaboration between the Faculty & the University Library - Johannessen, Lilja Marlen; Kristensen, Linn Kristine; Kalland, Kari (Septentrio Conference Series, 2021)
The Faculty of Health Sciences, OsloMet, launched the joint course “Introduction to Evidence-Based Practice (EBP) in Health Care” the fall semester 2020, to our knowledge, the first of its kind. The course is developed for all the Bachelor programmes at the Faculty which are part of RETHOS (National guidelines for the Health and Social Studies), and 350 have participated so far. This new course, which is mandatory(5 credits), teaches students about the rationale for evidence-based practice (EBP) and its Core Competencies: 1. Reflection (identify information needs) 2. Asking questions 3. Acquire (finding the evidence, literature search) 4. Appraise and Interpret (critical appraisal) 5. Apply(implementation) 6. Evaluate The course provides a foundation for learning and applying more advanced and field-specific skills. The teaching is designed with "flipped classroom", "team-based", "case based" and “peer instruction” learning activities in class and smaller groups. Digital learning resources are made available to the students in advance, through Canvas. The lectures can beheld as both physical and digital sessions, which facilitates great flexibility regarding size of the classes. Librarians with broad experience and competence in teaching EBP to health sciences students have been part of the working group developing this course from the start, alongside Faculty staff. This includes course descriptions, learning outcomes, parts of the exam paper, with a special responsibility for developing the teaching material covering the two core competencies Ask and Acquire. The librarians also cooperate with the faculty staff at “help desk”, where the students get feedback and guidance on their exam projects. The professional contribution from the University Library constitutes a significant part of the implementation of this course.This presentation will elaborate on the faculty-library collaboration, digital and active learning methods, both major key factors for successful implementation of this course